Perspectivas de inserção da energia solar fotovoltaica na geração de energia elétrica no Rio Grande do Norte - Wanderley, Augusto César Fialho (2013)
The generation of electricity in Brazil is predominantly renewable, with internal hydraulic generation being more than 70% of its energy matrix. The electricity rationing occurred in 2001 due to lack of rain, led the country to increase the participation of alternative energy sources. This need for new sources of energy makes the regional potential to be exploited, which configures the change of generation model from centralized generation to distributed generation. Among the alternative sources of energy, the solar energy is presented as very promising for Brazil, given that most of its territory is located near to the equator line, which implies days with greater number of hours of solar radiation. The state of Rio Grande do Norte (RN) has one of the highest levels of solar irradiation of the Brazilian territory, making it eligible to receive investments for the installation of photovoltaic solar plants. This thesis will present the state-of-the-art in solar photovoltaic power generation and will examine the potential for generation of solar photovoltaic power in Brazil and RN, based on solarimetrics measurements conducted by various institutions and also measurements performed in Natal, the state capital